EFFECTIVENESS OF BENSON RELAXATION THERAPY ON PAIN INTENSITY IN POST-SURGERY PATIENTS BENIGNATURE PROSTATE HYPERPLASIA (BPH) AT ABDUL MANAP HOSPITAL KOTA JAMBI - FEBRIA AZIZAH, TANIA; SULISTIAWAN, ANDIKA (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
BPH often causes disturbances in the elimination of urine because the enlarged prostate can put pressure on the bladder. According to the American Urology Association (2018) the incidence of experiencing symptoms of BPH has increased from a prevalence of 6.8 to 34.7 cases with 1,000 sufferers per year. The high prevalence and incidence of BPH requires an understanding of the management of BPH. The purpose of writing this case study is to carry out Nursing Care of Postoperative BPH clients with Acute Pain Problems at Abdul Manap Hospital, Jambi City. Methods This study used a method by collecting interview results, assessment data and results of observation of actions given Benson relaxation every morning for 5 consecutive days. Result : The intervention given is Benson relaxation which is carried out 5 times in 1 week, the patient feels the benefits of the Benson relaxation exercise where the client's balance/instability can be well controlled. Conclusion The intervention given was Benson relaxation given every morning for 5 consecutive days. Patients feel the benefits of Benson relaxation exercises where the client's pain can decrease.